ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN IMUNISASI DASAR LENGKAP PADA MASA PANDEMI COVID-19 DI PUSKESMAS KULISUSU - Lajumadil Akhmad Tiu; Asnia Zainuddin; Jafriati Jafriati (NHM PRESS, 2023)
North Buton Regency in 2019 is one of the districts that has the lowest complete Basic Immunization coverage in Southeast Sulawesi with a percentage of 73.70%. This research was carried out in the work area of ​​the Kulisusu Health Center, North Buton Regency. The analysis used in this study gradually included univariate, bivariate and multivariate analysis. Based on the results of the study, it can be concluded: There is no relationship between age and complete basic immunization during the COVID-19 pandemic; There is a significant relationship between low education and complete basic immunization during the COVID-19 pandemic; There is a significant relationship between lack of knowledge and complete basic immunization during the COVID-19 pandemic; There is a significant relationship between work and the completeness of basic immunization during the COVID-19 pandemic; There is a significant relationship between non-facility delivery places and complete basic immunization during the COVID-19 pandemic; There is a relationship between non-medical birth attendants and complete basic immunization during the COVID-19 pandemic; There is a significant relationship between the role of health workers who are not good with complete basic immunization during the COVID-19 pandemic; Factors that have a moderate relationship with complete basic immunization during the COVID-19 pandemic